1983
DOI: 10.1113/jphysiol.1983.sp014790
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of noradrenaline on the sodium‐potassium pump in isolated rat liver cells.

Abstract: SUMMARY1. Noradrenaline, which mobilizes Ca from intracellular stores, stimulated the Na-K pump in isolated rat liver cells. This resulted in transient decreases in internal Na content and external K concentration.2. The effect of the hormones was observed in the presence of the f8-adrenergic antagonist propranolol and was blocked by the a-antagonist phenoxybenzamine. Prazosin appeared to be 1000 times more potent than yohimbine in suppressing the cell response to the hormone, suggesting that the effect is med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…It therefore seems possible that the amidephrine-induced hypokalaemia is at least in part due to an a1-adrenoceptor induced K+-uptake, perhaps by the liver. Recent work with isolated liver cells of the rat has shown that oxl-adrenoceptor agonists, and other agents which elevate cytosolic Ca2+, increase the Na+/K+-pump rate which results in a net uptake of K+ (Capiod, Berthon, Poggioli, Burgess & Claret, 1982;Berthon, Burgess, Capiod, Claret & Poggioli, 1983). The time course and magnitude of this effect are comparable to the hypokalaemia found in vivo (see Figure 2) being maximal at 30s and returning to baseline within 3 to 5 min.…”
Section: Discussionsupporting
confidence: 63%
“…It therefore seems possible that the amidephrine-induced hypokalaemia is at least in part due to an a1-adrenoceptor induced K+-uptake, perhaps by the liver. Recent work with isolated liver cells of the rat has shown that oxl-adrenoceptor agonists, and other agents which elevate cytosolic Ca2+, increase the Na+/K+-pump rate which results in a net uptake of K+ (Capiod, Berthon, Poggioli, Burgess & Claret, 1982;Berthon, Burgess, Capiod, Claret & Poggioli, 1983). The time course and magnitude of this effect are comparable to the hypokalaemia found in vivo (see Figure 2) being maximal at 30s and returning to baseline within 3 to 5 min.…”
Section: Discussionsupporting
confidence: 63%
“…The present results are the first indication that, in common with noradrenaline (Burgess et al, 1981;Capiod et al, 1982Berthon et al, 1983, angiotensin and vasopressin rapidly stimulate the Na-K pump in rat isolated liver cells. The action ofeach hormone was dose-dependent, blocked by preincubation with the corresponding antagonist and occured via activation of different types of receptors (see also Campanile et al, 1982;Keppens et al, 1982;Jard, 1983).…”
Section: Discussionsupporting
confidence: 62%
“…In rat isolated liver cells, it has been shown that Rb behaves in a very similar way to K ions and can be used as a convenient substitue for K ions (Weiss & Putney, 1978;Ihlenfedt, 1981;Fehlmann & Freychet, 1981;Berthon et al, 1983). Routinely, a 1 ml sample (ca.…”
Section: Measurement Of Unidirectional 86rb Influxmentioning
confidence: 99%
See 2 more Smart Citations